2022
DOI: 10.1007/s10459-022-10100-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond empathy decline: Do the barriers to compassion change across medical training?

Abstract: Background: Despite being a mandated, foundational value in healthcare, research on compassion remains limited. Studying the individual, patient, clinical, and contextual factors that interfere with compassion—the “barriers”—may clarify our understanding of the origins of compassion and identify potential targets for improving patient-centred care. Studies of the related construct of empathy have suggested that medical students report declines with increasing clinical experience. In contrast, when comparing ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Our research also mirrors related research, which found that barriers to compassionate care seem to increase as students progress through medical school [ 61 ]. Our finding that time pressure and organisational culture contribute to a decline in empathy corroborates the extensive evidence on the inverse relationship between empathy and burnout among healthcare practitioners [ 2 , 3 , 62 65 ] and students [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our research also mirrors related research, which found that barriers to compassionate care seem to increase as students progress through medical school [ 61 ]. Our finding that time pressure and organisational culture contribute to a decline in empathy corroborates the extensive evidence on the inverse relationship between empathy and burnout among healthcare practitioners [ 2 , 3 , 62 65 ] and students [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…Compassionate caregiving has been described as involving meaningful actions to alleviate suffering and meet individual needs and prevent further suffering ( Durkin et al, 2021 ). Compassionate behaviors ( Straughair, 2019 ) are taught through pedagogy ( Hendry, 2019 ), learning objectives ( Lown, 2016 ; Sinclair et al, 2021 ; Wang et al, 2022 ) assessment ( Lown et al, 2016 ), and skills sets such as reflective listening ( Braillon and Taiebi, 2020 ; Su et al, 2021 ). Healthcare research has examined compassion from the perspective of: the predictors of compassion in healthcare professionals ( Fernando and Consedine, 2014 ; Bleiker et al, 2020 ; Pavlova et al, 2022 ); how care environment and organizational culture affect compassion ( Casagrande, 2016 ; Ali and Terry, 2017 ; Dev et al, 2019 ; Tehranineshat et al, 2019 ; Wiljer et al, 2019 ; Ali et al, 2022 ); compassion-maintaining strategies and interventions ( Blomberg et al, 2016 ; Terry et al, 2017 ; Flores and Brown, 2018 ; Baguley et al, 2020 ; Hopkins et al, 2021 ; Malenfant et al, 2022 ); compassionate leadership ( Dewar and Cook, 2014 ; de Zulueta, 2015 ; Lown et al, 2019 ; West et al, 2020 ); and regulation of compassionate caregiving ( Harris et al, 2019 ; Pedersen and Roelsgaard Obling, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A steep decline in empathy occurs with the greatest frequency in the clinical years of medical school. Psychological protections to decrease burnout and emotional distress may result in medical students dissociating from patients and creating barriers that diminish kindness in patient-doctor interactions [3].…”
Section: Editorialmentioning
confidence: 99%